Non-Performing Loans and Stock Prices: A Case of Nepali Commercial Banks - Shrestha, Niyam Raj (PYC Nepal Journal of Management, 2011)
The article attempts to ascertain the determinants of nonperforming loans (NPL) in the Nepalese commercial banking sector using a descriptive statistics, trend and one factor econometric model. The study has selected 18 Nepal commercial banks by using stratified sampling method, and found the aggregate values of ratio that measures the banks’ health. The results show that aggregate NPL of commercial banks is in decreasing trend and the model is consistent with priori of the NPL to its stock price. This indicates that every rupee appreciation in the NPL brings about stock price decrease by 0.528 rupee. The study has shown an increasing trend of the total performing loan to total deposit ratio in the industry, while NPL is on the decline. It has given positive indication that the banks are able to mobilize their deposit in productive sectors.